Church and Society. The Role of Religious Journals in the Difusion of the Biblical Element within the Historical Banat area. 1867-1918 - Scridon, Alin Cristian (Journal of Education Culture and Society, 2020)
The church press published important documents regarding the religious life of Romanians from Transylvania and Banat. This publication also included details regarding the religious life of the school from Banat. The Biserica şi Şcoala magazinewas published in the western historical Banat, in Arad. This was possible due to the fact that Timisoara, the most important city in Banat, had a Romanian Orthodox Deanery that was dependent on the Diocese of Arad, before the establishment of the Diocese of Timisoara in 1939.The Caransebes Diocese’ magazine Foaia Diecezană (The Diocesan Sheet) provided the clergy and the faithful with information on Christian spirituality. Along the aforementioned magazines, there were a few newspapers which have enriched this field’s literature. Based on those covered by the study, we find that the media made an overwhelming contribution to the dissemination of the biblical information during that particular period of time.